The dialects of the tribes in the books of times, places, and clans, a comparative study - Khalifa, Ali .A; Abed, Zaidoon F. (Al-Adab Journal, 2015)
Abstract :This paper studies a group of dialects of arab tribes that have been mentioned in the sources of times and places to the end of hijri sixth century . trough our investigation for the linguisticsections that their authors dealt with , we have found that thay mention many dialects of different arab tribes especially the standard ones . their researd approaches for these dialects were varied. Some times they named one dialect, or mentioned two dialects for the some word or some times they declared one of them and just refer to the second with out mentioning to which of them it belonged .thay might preferone of the dialects that they mentioned . The study has been divided in to standard dialects and weak dialects which are fewer.